The Influence of Employee Wellbeing and Employee Resiliance on Innovation Work Behaviour Mediated by Work Climate in the Insurance Industry in DKI Jakarta - Zeanette Tiarma Lisbet (ARKA INSTITUTE, 2023)
This study aims to analyse the influence of employee wellbeing and employee resiliance on innovation work behavior mediated by work climate in the insurance industry in DKI Jakarta. The population of this study are all employees of companies who work in the essential sector of DKI Jakarta, especially in life insurance and general insurance companies. The sampling method used non-probability sampling with purposive sampling technique. the minimum sample size in this study was 250 respondents. The data analysis method used Structural Equation Model (SEM) analysis with the AMOS version 20 statistical program. Based on the test results it can be concluded that employee wellbeing does not had a positive effect on innovation work behavior. employee resilience had a positive effect on innovation work behavior. Furthermore, it is found that employee wellbeing and employee resilience had a positive effect on hybrid work climate, while hybrid work climate had no effect on innovation work behaviour. In testing the intervening hybrid work climate found that it can mediate the effect of employee wellbeing on innovation work behaviour. While the hybrid work climate cannot mediate the effect of employee resilience on innovation work behaviour on all employees of companies working in the essential sector of DKI Jakarta.